STRATEGI CUSTOMER RELATIONS DALAM MENINGKATKAN KEPUASAN PELANGGAN PADA HOTEL DYAN GRAHA PEKANBARU - ATIKA, RISMA DIAN; ", NURJANAH (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Hotel is an industry engaged in the field of specialty services, where the services are crucial to giving satisfaction to customers. The growth of new hotels makes these hotels and more aggressively to improve service quality in order to satisfy customer expectations. Creation of customer satisfaction and will deliver benefits to both the hotel 's reputation in the eyes of customers and also the profits from the hotel will increase. Based on the explanation above, the problem in this research is how customer relations strategy to improve customer satisfaction Hotel Dyan Graha Pekanbaru .This study used qualitative research methods and data collection techniques are participating observation, interviews and documentation. Once data is collected, the authors use an interactive model of data analysis proposed by Miles and Huberman. According to this model ,there are three types of analysis, namely data reduction, data display and conclusion drawing or verification and data collection activities it is a cyclical and interactive. The final stage of this analysis is the examination of the validity of the data entered .From the research that has been done, there is a series of processes in determining the strategy situation analysis, program planning, action and communication and evaluation. While the strategies used to improve customer satisfaction is the family gathering, social programs responsibility and promotion programs. Furthermore, the authors found several factors according to customer relations strategy strengths SWOT analysis such as hotel competition, competitive prices, complete lack of facilities and services that are less satisfactory. While the weakness factor are the promo offer, promotion through the media , means of communication, co-operation with other companies, and locations .Keyword : strategy, customer relations, customer relations strategy ,customer statisfaction